Mechanistic Insights into Antioxidant and Antimicrobial Actions of Citrus and Medicinal Plant-Based Extracts for Meat Preservation - Gnanavel, G; A, Prathika; P, Ardra; T, Thansimol; S, Arivumathi (Journal of Neonatal Surgery, 2025)
The application of natural preservatives, especially citrus extracts and plant-source essential oils, has developed into a viable option compared to synthetic preservatives to extend the lifespan of flesh products. With high levels of bioactive compounds, natural preservatives are recognized for having excellent antioxidant and antimicrobial activity, inhibiting microbial growth and hindering lipid oxidation. According to studies, citric-based preservatives, i.e., lemon, lime, and pomelo peel extracts, were greatly effective in achieving shelf life under different storage conditions. Importantly, treating citrus extracts with an oxygen absorber (0.1-0.2 ml/100g) increased the lifespan of ground chicken by about 4 to 6 days at 4°C. Adding lime peel extracts containing 0.25% oil effectively maintained the standard of chicken cakes when kept at 4°C for nine days. Lemongrass, chitosan, and citrus essential oil nano-emulsion coatings (1.5%) also increased chicken breast fillets' lifespan by 5 days through cold storage. A comprehensive meta-analysis found that incorporating citrus additives at concentrations ranging from 0.2% to 1.5% effectively extended the lifespan of raw chicken flesh by 21 days under refrigeration at 4°C. Other treatments, including citrus by-product extracts (5 mg/mL) and alginate films carrying cinnamon and rosemary essential oils (5 mg/mL), successfully extended lifespan by 9 days and 2 days, respectively. These findings indicate that the highest-performing concentrations of citrus-based additives promise to improve meat preservation by slowing spoilage and preserving sensory characteristics. Combining natural preservatives with novel delivery systems, such as nanoemulsion, presents a valuable strategy for the meat industry to address consumer pressure for clean-label, naturally preserved products. There is a need for future studies to optimize such methods for wider-scale commercial application, mitigating sensory impacts and regulatory requirements.